Differential parasitism of native and invasive widow spider egg sacs. (16th March 2022) - Mowery, Monica A; Arabesky, Valeria; Lubin, Yael; Segoli, Michal
Abstract: During colonization, invasive species establish and spread to new locations, where they may have an advantage over native species. One such advantage may be avoidance of predators or parasites by means of better defenses or due to lower suitability as a host. We conducted field surveys and lab behavioral experiments to investigate the differential susceptibility of two widow spider species—one native to Israel, the white widow spider Latrodectus pallidus, and one invasive species, the brown widow spider, Latrodectus geometricus —to an egg sac parasitoid wasp, Philolema latrodecti . In collections of egg sacs from six paired sites of L. geometricus and L. pallidus populations in the Negev Desert, Israel, we found higher parasitism rates on the egg sacs of the native L. pallidus . In no-choice trials, we found that wasps were more likely to parasitize and oviposited longer on L. pallidus egg sacs than on L. geometricus egg sacs. In two-choice tests with spider webs and egg sacs, parasitoids made first contact with L. pallidus webs more often and faster. After developing inside of L. pallidus egg sacs, more parasitoids emerged and were larger than those emerging from L. geometricus egg sacs. Potentially better defense of the L. geometricus egg sacs as well as the parasitoid's fitness advantages gained from parasitizing L. pallidus egg sacs may explain the higher parasitism rate in the native species. Our results suggest that the invasion and establishment success of L. geometricus is due, in part, to its ability to escape parasitism. Abstract : Highly successful invasive brown widow spiders avoid egg sac parasitism. We found that parasitoids prefer native widow spider egg sacs compared to those of the invasive brown widow spider. More and larger wasps emerged from the native widow egg sacs, indicating that the species is a better host for the wasp. The lower suitability of brown widow egg sacs for the wasp parasitoid may explain the rapid invasive spread of brown widow spiders worldwide.